Eloping Women’s Dignity in the Novels Nawi Cinta Inah and Mangalua: A Multicultural Feminism Study - Heru SP Saputra; Titik Maslikatin; Edy Hariyadi; L Dyah Purwita Wardani SWW (Leksema: Jurnal Bahasa dan Sastra, 2026)
This article examines the dignity of women in the Indonesian tradition of elopement—melayoken (Using/Osing) and mangalua (Batak Toba)—as represented in two novels: Nawi Cinta Inah, written by Antariksawan Jusuf and Hani Z Noor, and Mangalua by Idris Pasaribu. Using multicultural feminism, this study reads the text as a cultural artifact shaped by—and simultaneously shaping—local social structures. Methodologically, close reading is combined with hermeneutic procedures and triangulated with ethnographic findings on Using and Batak customs. Mohanty's critique of feminist universalism highlights contextualized everyday practices of resistance; Narayan's notion of “tradition as negotiation” and warnings against “death by culture” guide an empathetic reading of agency within the customary framework. The findings demonstrate that elopement is not reduced to oppression or absolute freedom; it functions as an arena of negotiation where women articulate choice and responsibility, then seek legitimacy through customary reconciliation (colok/Using; uhum/Batak). This study contributes a culturally sensitive feminist reading of Indonesian literature and suggests an expansion of comparative studies to other Nusantara traditions as well as studies of reader reception.